Cardiac Cell Therapy and Bypass Surgery - Choi, Yeong-Hoon; Nasseri, Boris; Stamm, Christof (Current Pharmaceutical Design, 2011)
More than 10 years ago, the first clinical application of cardiac cell therapy was performed in a patient undergoing coronary bypass grafting (CABG). Ever since, catheter-based cell delivery approaches have dominated the field, but surgical cell therapy continues to provide important information on safety and efficacy of various cell therapy strategies. The open chest offers unrivalled simplicity and precision of intramyocardial cell injection, and the cardiac surgical patient population includes those with very advanced heart disease who are in greatest need of innovative regeneration concepts. In this review, the clinical experience with cardiac surgical cell therapy is summarized and critically appraised.
Keywords: Stem cell